ANALISIS PROSES PEMBELAJARAN TEMATIK DI KELAS V SDN 4 SEKURO MLONGGO JEPARA - Vidiansyah Nahrukhin; Aan Widiyono; Naili Rofiqoh (LPPM Universitas Bina Bangsa, 2022)
The aims of this study are: (1) to analyze the thematic learning process in class V SDN 4 Sekuro Mlonggo Jepara. (2) To analyze the supporting factors and inhibiting factors of the thematic learning process in class V SDN 4 Sekuro Mlonggo Jepara. The research approach used is qualitative with descriptive research type. Data collection techniques in this study are observation, interviews and documentation. The results of this study indicate that the thematic learning process in class V SDN 4 Sekuro Mlonggo Jepara starts from changing the curriculum from KTSP to K-13. Thematic learning at SDN 4 Sekuro Mlonggo Jepara specifically for class V is quite good in thematic learning, although there are still shortcomings, namely using teaching materials in a separate approach. Meanwhile, the supporting and inhibiting factors in the thematic learning process in class V SDN 4 Sekuro Mlonggo Jepara. Namely, the supporting factors of the curriculum components, lesson plans, syllabus and textbooks provided from the school. While the inhibiting factor is teaching materials that still use a separate approach